2020
DOI: 10.1001/jama.2020.8051
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Health Equity—A New Kind of “Herd Immunity”

Abstract: Three articles recently published in JAMA provide insight into the large racial/ethnic differences associated with coronavirus disease 2019 (COVID-19) and highlight the need for, and potential opportunity to, redouble efforts in the US to develop strategies that would enable society to slow and ultimately eliminate the spread of inequities in health. 1-3 COVID-19 is a magnifying glass that has highlighted the larger pandemic of racial/ethnic disparities in health. For more than 100 years research has documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
231
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 247 publications
(237 citation statements)
references
References 16 publications
(33 reference statements)
4
231
0
2
Order By: Relevance
“…Among patients with recent diagnosis of SUD, African Americans had significantly higher risk of COVID-19 than Caucasians, an effect that was strongest for African Americans with OUD and they also had worse outcomes (death and hospitalizations). This is consistent with data from states and counties across the US showing that the coronavirus affects African Americans at a disproportionately high rate and that the they suffer a greater death toll [28][29][30][31]. We showed that adult African Americans with recent diagnosis of SUDs had higher prevalence of asthma, chronic kidney disease, type 2 diabetes, hypertension, obesity and HIV compared to adult Caucasians.…”
Section: Discussionsupporting
confidence: 89%
“…Among patients with recent diagnosis of SUD, African Americans had significantly higher risk of COVID-19 than Caucasians, an effect that was strongest for African Americans with OUD and they also had worse outcomes (death and hospitalizations). This is consistent with data from states and counties across the US showing that the coronavirus affects African Americans at a disproportionately high rate and that the they suffer a greater death toll [28][29][30][31]. We showed that adult African Americans with recent diagnosis of SUDs had higher prevalence of asthma, chronic kidney disease, type 2 diabetes, hypertension, obesity and HIV compared to adult Caucasians.…”
Section: Discussionsupporting
confidence: 89%
“…Hand hygiene is vital to prevent the spread of infection. Racial and ethnic minorities continue to face a lack of indoor plumbing [ 15 ]. Indigenous peoples, African-American, and Hispanics are much more likely than Caucasian households to lack access to complete plumbing, electricity, & sanitation among other essential amenities.…”
Section: Discussionmentioning
confidence: 99%
“…However, misinformation, oversight, and delayed mitigation strategies alone do not fully explain differential COVID-19 incidence. Many have deeply analyzed the effect of social determinants on COVID-19 disparities (15,65,66). This historical inheritance, of which the 1918 influenza pandemic forms just 1 episode, shapes how social conditions obstruct minority participation in public health mitigation and containment measures.…”
Section: History Of Medicinementioning
confidence: 99%